2020
DOI: 10.1162/dint_a_00049
|View full text |Cite
|
Sign up to set email alerts
|

Towards the Tipping Point for FAIR Implementation

Abstract: This article explores the global implementation of the FAIR Guiding Principles for scientific management and data stewardship, which provide that data should be findable, accessible, interoperable and reusable. The implementation of these principles is designed to lead to the stewardship of data as FAIR digital objects and the establishment of the Internet of FAIR Data and Services (IFDS). If implementation reaches a tipping point, IFDS has the potential to revolutionize how data is managed by making machine a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(56 citation statements)
references
References 11 publications
0
56
0
Order By: Relevance
“…These principles are expected to systematically facilitate both humans and their machines to discover, get access to, integrate, and analyse scientific data and other scholarly digital objects such as algorithms, code, and workflows that led to published data, among others (Wilkinson et al, 2016). At present, nevertheless, there are concerns over the paucity of their implementation outside the European continent and their relatively limited application in natural science (Van Reisen et al, 2020). This study also reports that there is still important work to do to reach the FAIR tipping point, namely: (1) solving some 49 OPEN/DATA-DRIVEN SCIENCE IN BED FORM DYNAMICS problems regarding FAIR implementation (e.g.…”
Section: Tackling the Technical Challengesmentioning
confidence: 99%
“…These principles are expected to systematically facilitate both humans and their machines to discover, get access to, integrate, and analyse scientific data and other scholarly digital objects such as algorithms, code, and workflows that led to published data, among others (Wilkinson et al, 2016). At present, nevertheless, there are concerns over the paucity of their implementation outside the European continent and their relatively limited application in natural science (Van Reisen et al, 2020). This study also reports that there is still important work to do to reach the FAIR tipping point, namely: (1) solving some 49 OPEN/DATA-DRIVEN SCIENCE IN BED FORM DYNAMICS problems regarding FAIR implementation (e.g.…”
Section: Tackling the Technical Challengesmentioning
confidence: 99%
“…An analysis of the INs of GO FAIR to date demonstrates a geographic bias of implementation in Europe, reflecting perhaps the leadership provided to it by the European Commission. Comparative literature review of a hundred articles citing FAIR principles, published in the period 2016-2019, shows the current delay in Africa on FAIR-implementation, and its overwhelming concentration centred in Europe and the US [3]. Analysis of domain areas addressed both in INs and in the hundred journal articles reporting on FAIR implementation and analysed in a literature review showed a clear focus on implementation in the life sciences and natural sciences.…”
Section: Introduction: Expanding the Internet Of Fair Data And Services For Digital Health To Africamentioning
confidence: 99%
“…[2] The implementation of FAIR is supported by the GO FAIR Implementation Networks. This recognises the dynamic process of its construction [3]. The GO FAIR International Support and Coordination Office (GFISCO) supports the Implementation Networks (INs): "a consortium committed to defining and creating materials and tools as elements of the Internet of FAIR Data and Services (IFDS)" [4].…”
Section: Introduction: Expanding the Internet Of Fair Data And Services For Digital Health To Africamentioning
confidence: 99%
“…There are emerging design principles for managing digital resources in the infrastructure landscape, such as findable, accessible, interoperable, and reusable (FAIR) principles for data repositories. We qualify them as emergent as FAIR principles as research communities still discuss and seek to implement FAIR principles (van Reisen et al, 2019). Therefore, the design of information systems for open science is a novel and explorative inquiry.…”
Section: Mrq: How Can We Organize Research Data Management For Presermentioning
confidence: 99%
“…Therefore, a significant part of improving research resides in how scientific data, software, and other relevant material can be better preserved and shared between scientific communities to make research communication more transparent and reproducible (Prager et al, 2019). In consequence, a crucial element of the success of OS is the proper management (also known as stewardship) of Introduction -5 - (van Reisen et al, 2019). The recent uptake of research data management (RDM), as a means for funders to (partly) correct these inefficiencies, is an intriguing attempt to transform scientific practice.…”
Section: Introduction Chaptermentioning
confidence: 99%